Paradise lies at the feet of the mother - Percival, John; British Broadcasting Corporation; Ambrose Video Publishing (New York : Ambrose Video Publishing, 1993)
Explores the position of women and the role of family under Islamic law and how much of this is laid down by law and how much comes from cultural traditions
Film editor, Noel Chanan ; videotape editor, Peter Dunkley ; music, Rohan ; consultant, Akbar Ahmed.
Host: Akbar Ahmed.
Keywords: Women in Islam; Women -- Legal status, laws, etc